Pengaruh Penggunaan Media Manipulaif Berbasis Pendekatan Saintifik Terhadap Pemahaman Konsep Matematika Peserta Didik Kelas VIII SMPN 13 Padang - NIKMATHUL FAUZIA (Jurnal Edukasi dan Penelitian Matematika, 2020)
Understanding of mathematical concepts is one of the purpose in mathematics learning. Understanding of mathematical concepts is the foundation for students to understand mathematics. But infact, Understanding of mathematical concepts  of students at second grade SMPN 13 Padang waslow. It is caused by learning model that used has not facilitated students to develop their Understanding of mathematical concepts.One effort to overcome this problem is by using manipulatives to teach Pythagorean theorem.This manipulative helps students to Understanding of abstract mathematical concepts. The type of research is a pra-experimental design with One Group Pre test-Post test Design. The research hypothesis is carried out by using the paired sample t-test. These results indicate that the ability of students’ understanding mathematical concepts in learning that using manipulatives is better than the ability of students’ understanding mathematical concepts in learning that apply direct learning.                                                                      Keywords – Understanding of mathematical concepts, the use of manipulatives, Direct Learning